Possible Application of Activated Palm Kernel Shell (APKS) from Palm Oil Industry as Potential Filler in Carboxylated Nitrile Butadiene Rubber (XNBR) - Mamauod, Siti Nur Liyana; Zainal Rashid , Syazwani Aqilah; Zainal , Nahrul Hayawin; Ismail, Hanafi (Environment-Behaviour Proceedings Journal, 2024)
In this study, different APKS loadings from 0 phr to 50 phr were incorporated into the carboxylated butadiene rubber (XNBR). The average filler particle size was identified as between 1.217 to 31.944μm based on particle size analysis. The curing, crosslink density, tensile properties, and morphology values of the APKS-filled XNBR were studied. The incorporated APKS has increased the crosslink density, delta torque, cure time (t90), and decreased the swelling degree of the XNBR. The overall mechanical properties were enhanced due to the mechanical interlocking of rubber-filler phases until the optimum APKS loading which was 40 phr.